Model Based Change Detection of Water Body Using Landsat Imagery: A Case Study of Rajshahi Bangladesh: DOI: 10.32526/ennrj.18.4.2020.33 - Ahammad, Tofayel; Rahaman, Hafizur; Refat Faisal, B.M.; Sultana, Nasrin (Environment and Natural Resources Journal, 2020)
The aim of this study is to detect water bodies which include ponds, lake, river, canal, irrigation land etc. from Landsat TM (Thematic Mapper) &OLI (Operational Land Imager) data by Pixel Based Model (PBM) for the year 2010 and 2017 and to identify the changed area of water body from 2010 to 2017. Rajshahi division of Bangladesh was selected as study area for this case study. Landsat 5 data acquired on 21 & 28 January 2010 and Landsat 8 data acquired on 15 & 24 January 2017 were used as satellite imagery for this analysis. Two images of each month were then mosaicked to find a new image which cover whole Rajshahidivision. Lowest and highest pixel of the water body for the each band was investigated. Then a Pixel Based Model (PBM) was formed by using the entireLandsat band and run the model. The result was shown a binary image which includes water body and non-water body. Also common area, newly formed area& abolished area of water bodywere identified by using PBMmodel. Theresult indicates that water land is decreased 3.74% in 2017 than 2010 , 56.52% area of water body converted into non-water body in 2017 and 45.33% new water body is formed in 2017. The unchanged area of water body is 1, 02,671hectors which is present both in 2010 & 2017.